Vaccine construction for human papilloma virus (HPV) type 16 and 18 Infection using in silico approach to combat cervical cancer - Dharmawan, Muhammad Alsyifaa; Ansori, Arif Nur Muhammad; Dian, Farida Aryani; Probojati, Rasyadan Taufiq; Tamam, Muhammad Badrut; Kharisma, Viol Dhea (Generasi Biologi Indonesia, 2021)
Human papillomavirus (HPV) is a virus that causes infection on the surface of the skin and has the potential to cause cervical cancer. This viral infection is characterized by the growth of warts on the skin in various areas of the body, such as the arms, legs, mouth, and genital area. Because the virus can endanger health, it is necessary to design an HPV vaccine to overcome this problem. In this study, we performed a study characterization of HPV types 16 and 18 sequences to obtain immunogenic epitopes retrieved from the National Center for Biotechnology Information (NCBI) web server. Then, epitope prediction was performed using the immune epitope database (IEDB) web server and selected to get the best vaccine candidate for HPV types 16 and 18. We recommend 16P1 as an epitope-based peptide vaccine candidate for HPV type 16 and 18P4 for type 18. Both vaccine candidates are antigenic, non-allergenic, and non-toxic. The 16P1 and 18P4 have the lowest global energy values ​​among the other candidates. However, further research is needed to be able to develop the best vaccine (in vitro and in vivo experiments).